Human Osteoclasts are Inducible Immunosuppressive Cells in Response to T cell–Derived IFN‐γ and CD40 Ligand In Vitro. (December 2014) - Li, Haiyan; Lu, Yong; Qian, Jianfei; Zheng, Yuhuan; Zhang, Mingjun; Bi, Enguang; He, Jin; Liu, Zhiqiang; Xu, Jingda; Gao, Jerry Y; Yi, Qing
ABSTRACT Osteoclasts (OCs) are bone resorbing cells whose activity can be regulated by activated T cells and their cytokines. However, the immune function of OCs is largely unknown. In this study, we found that as bystanders, human OCs effectively suppressed T‐cell proliferation induced by allogeneic, microbial antigenic, and T‐cell receptor stimuli in vitro. Mechanism studies revealed that T cell–derived IFN‐γ and CD40 ligand (CD40L) induced the expression of indoleamine 2, 3‐dioxygenase (IDO) in OCs, which mediated the immunosuppressive function on T‐cell proliferation through depleting tryptophan. Neutralizing IFN‐γ and blocking CD40L, or silencing or inhibiting IDO in OCs restored T‐cell proliferation in the presence of OCs. Our data reveal a novel function of human OCs as inducible immunosuppressive cells, and a feedback loop between OCs and activated T cells. Thus, this study provides new insight into the mechanism of the immunosuppressive function of OCs, and may be helpful for developing novel therapeutic strategies for human diseases involving both the bone and immune systems. © 2014 American Society for Bone and Mineral Research.